Advanced simulation based methods for optimal stopping and control : with applications in finance (Palgrave Macmillan, 2018)
This is an advanced guide to optimal stopping and control, focusing on advanced Monte Carlo simulation and its application to finance. Written for quantitative finance practitioners and researchers in academia, the book looks at the classical simulation based algorithms before introducing some of the new, cutting edge approaches under development.